1998
DOI: 10.1021/om9801610
|View full text |Cite
|
Sign up to set email alerts
|

Insertion of a Water Oxygen Atom into a Phosphorus−Metal Bond:  From a P-Coordinated (Diphenylphosphino)alkyne to a Coordinated η2(O,C)-Vinyldiphenylphosphine Oxide

Abstract: The reaction of [(Fp)Ph2PC⋮CR][BF4] (Fp = (C5H5)Fe(CO)2; R = H (1), Me (2), tBu (3), Ph (4), Tol (5)) with (CH3)3NO·2H2O (6) was studied, and the new complexes [CpFe(CO)(η2(O,C)-Ph2P(O)CHCR)] (R = Ph (7), Tol (8)) were isolated. Compound 8 was characterized by X-ray diffraction. An isotopic labeling study showed that the oxygen atom bonded to phosphorus came from a water molecule.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…For example, [(η 5 -C 5 H 5 )Ni] 2 (PPh 2 (O)C 2 CF 3 ), the first acetylenic phosphine oxide π complex structurally characterized, was obtained as one byproduct in the reaction of [(η 5 -C 5 H 5 ) 2 Ni] with PPh 2 Ct CCF 3 . 79 More recently, a cationic iron P-coordinated (diphenylphosphino)alkyne complex [(C 5 H 5 )Fe(CO) 2 (PPh 2 CtCPh)]-(BF 4 ) was oxidized to an iron vinyldiphenylphosphine oxide 81 and the η 2 -alkynylphosphine complex [Pt(η 2 -PPh 2 CtCMe)-(dcpe)] was oxidized in air to the corresponding phosphine oxide complex [Pt{η 2 -PPh 2 (O)CtCMe}(dcpe)]. 9 To check the possibilities of insertion in other systems, we have examined the reactions of the catecholate and dithiolate complexes 6 and 7 with cis-[Pt(C 6 F 5 ) 2 (THF) 2 ] in 1:1 and 1:2 molar ratios.…”
mentioning
confidence: 99%
“…For example, [(η 5 -C 5 H 5 )Ni] 2 (PPh 2 (O)C 2 CF 3 ), the first acetylenic phosphine oxide π complex structurally characterized, was obtained as one byproduct in the reaction of [(η 5 -C 5 H 5 ) 2 Ni] with PPh 2 Ct CCF 3 . 79 More recently, a cationic iron P-coordinated (diphenylphosphino)alkyne complex [(C 5 H 5 )Fe(CO) 2 (PPh 2 CtCPh)]-(BF 4 ) was oxidized to an iron vinyldiphenylphosphine oxide 81 and the η 2 -alkynylphosphine complex [Pt(η 2 -PPh 2 CtCMe)-(dcpe)] was oxidized in air to the corresponding phosphine oxide complex [Pt{η 2 -PPh 2 (O)CtCMe}(dcpe)]. 9 To check the possibilities of insertion in other systems, we have examined the reactions of the catecholate and dithiolate complexes 6 and 7 with cis-[Pt(C 6 F 5 ) 2 (THF) 2 ] in 1:1 and 1:2 molar ratios.…”
mentioning
confidence: 99%
“…Solvents were distilled under nitrogen from appropriate drying agents and degassed prior to use. 24 Infrared spectra were recorded in hexane solution in 0.5 mm NaCl cells, using a Perkin-Elmer 1710 Fourier-transform spectrometer, fast atom bombardment (FAB) mass spectra on a Kratos MS 890 instrument using 3-nitrobenzyl alcohol as a matrix, proton (reference to SiMe 4 ), 31 P and 13 C NMR spectra on either a Bruker WM250 or AM400 spectrometer; 31 P NMR chemical shifts are referenced to 85% H 3 PO 4 . Preparative thin-layer chromatography (TLC) was carried out on commercial Merck plates with a 0.25 mm layer of silica, or on 1 mm silica plates prepared at the Department of Chemistry, Cambridge.…”
Section: General Techniquesmentioning
confidence: 99%
“…However, further studies with a broad range of metal complexes have revealed other interesting abilities of these ligands such as the preparation of metal complexes with uncoordinated alkynes [2][3][4], intramolecular coupling of the alkynyl moieties [5][6][7], insertion of the triple bond in M-H or M-C bonds [8,9], preparation of heterometallic compounds [6,[10][11][12], or the development of new materials [13]. These ligands can also lead to the formation of metallacycles by means of a reaction between the alkyne and another ligand linked to metal [9,14,15]. We reported some years ago that cationic P-coordinated iron complexes [(C 5 H 5 )Fe-(CO) 2 (Ph 2 PC"CR)] + can lead to the formation of metallacycles in mild conditions, giving good yields by the reaction pathway shown in Scheme 1 [15].…”
Section: Introductionmentioning
confidence: 99%
“…These ligands can also lead to the formation of metallacycles by means of a reaction between the alkyne and another ligand linked to metal [9,14,15]. We reported some years ago that cationic P-coordinated iron complexes [(C 5 H 5 )Fe-(CO) 2 (Ph 2 PC"CR)] + can lead to the formation of metallacycles in mild conditions, giving good yields by the reaction pathway shown in Scheme 1 [15].…”
Section: Introductionmentioning
confidence: 99%